Transvaginal Ultrasonography Is the Diagnostic Method for Evaluation of Abnormal Uterine Bleeding (Journal of Shaheed Suhrawardy Medical College, 2012)
Objective: The objective of this study is to assess the utility of transvaginal iiltrasonography in patients presenting abnormal uterine bleeding. Materials and methods: Between July 2000 to December 2000, 50 patients underwent transvaginal sonography (TVS) for abnormal uterine bleeding. All patients had transvaginal sonography before histopathology. On TVS, the sonographic appearance of the endometrium was classified according to the following parameters: normal or abnormal thickness, homogeneous or heterogeneous echogenicity, bulbous contour, discontinuous, or obscured. A comparison was performed between TVS with histopathology. Results: The most common causes for the abnormal uterine bleeding were leiomvoma in TVS (42.0%). Other causes were dysfunctional uterine bleeding (28.0%), adenomyosis (6.0%). endometrialpolyp (4.0%), thin atrophic endometrium (8.0%), endometrial hyperplasia (8.0%). and endometrial carcinoma (4.0%). After histopathologic evaluation 40.0% patients had leiomvoma, 24.0% DUB, 10.0% adenomyosis, 8.0% endometrial polyp, 8.0% thin atrophic endometrium, 6.0% endometrial carcinoma and 4.0% endometrial hvperplasia. Comparing the TVS with histopathologic findings, TVS had a sensitivity of 94.3%, specificity of 80.0%, accuracy of 90.0%, PPVof91.6% andNPVof 85.7%. Conclusion: TVS is an easy, safe, rapid and tolerable procedure. It has an excellent diagnostic accuracy in the diagnosis of uterine pathology responsible for abnormal uterine bleeding. Abbreviation: TVS transvaginal sonographv; AUB abnormal uterine bleeding; DUB dysfunctional uterine bleeding, PPV positive predictive value, NPV Negative predictive value. Journal of Shaheed Suhrawardy Medical College Vol 2No.1 June 2010 page 10-12 DOI: http://dx.doi.org/10.3329/jssmc.v2i1.12344